Analysing the attributes of Comprehensive Cancer Centres and Cancer Centres across Europe to identify key hallmarks - Kehrloesser, Sebastian; Oberst, Simon; Westerhuis, Willien; Wendler, Astrid; Wind, Anke; Blaauwgeers, Harriët; Burrion, Jean-Benoit; Nagy, Péter; Saeter, Gunnar; Gustafsson, Eva; De Paoli, Paolo; Lovey, József; et al. (Molecular oncology, 2021)
There is a persistent variation in cancer outcomes among and within European countries suggesting (among other causes) inequalities in access to or delivery of high-quality cancer care. European policy (EU Cancer Mission and Europe's Beating Cancer Plan) is currently moving towards a mission-oriented approach addressing these inequalities. In this study, we used the quantitative and qualitative data of the Organisation of European Cancer Institutes' Accreditation and Designation Programme, relating to 40 large European cancer centres, to describe their current compliance with quality standards, to identify the hallmarks common to all centres and to show the distinctive features of Comprehensive Cancer Centres. All Comprehensive Cancer Centres and Cancer Centres accredited by the Organisation of European Cancer Institutes show good compliance with quality standards related to care, multidisciplinarity and patient centredness. However, Comprehensive Cancer Centres on average showed significantly better scores on indicators related to the volume, quality and integration of translational research, such as high-impact publications, clinical trial activity (especially in phase I and phase IIa trials) and filing more patents as early indicators of innovation. However, irrespective of their size, centres show significant variability regarding effective governance when functioning as entities within larger hospitals.
Keywords: quality standard; onkologická péče - zařízení; Cancer Care Facilities; Europe; týmová péče o pacienty; Cohort Studies; Evropa; Medical Oncology; Patient Care Team; kvalita zdravotní péče; multidisciplinarity; Quality of Health Care; kohortové studie; translational research; péče orientovaná na pacienta; Neoplasms; akademie a ústavy; Patient-Centered Care; clinical trials; comprehensive cancer center; Humans; nádory; Academies and Institutes; Translational Research, Biomedical; biomedicínský výzkum; accreditation; translační biomedicínský výzkum; lékařská onkologie; lidé; Biomedical Research